Profil Metrik Pusat Melanomakrofag pada Limpa Ikan Mas (Cyprinus carpio) yang Terpapar Merkuri Klorida - Tasyarrafa Naf'a Solakhiyah; Wahju Tjahjaningsih; Laksmi Sulmartiwi (Airlangga University, 2023)
Increasing the number of heavy metals in the aquatic environment results in the accumulation of contaminants in fish body tissue, making fish an ideal bio-indicator of environmental pollution. The spleen included in the hematopoietic tissue contains macrophages. Macrophages form aggregates that contain pigments referred to melanomacrophage centres (MMCs). This research aims to analyse the metric profiles of MMCs on the common carp (Cyprinus carpio) spleen as a non-specific cellular immune response against mercury chloride exposure. This study used a Completely Randomized Design method with four treatments at different concentrations of mercury chloride (HgCl2) of 0 mg.l-1 , 0.01 mg.l-1 , 0.05 mg.l-1 , and 0.1 mg.l-1 . Each treatment was replicated five times. Data on the number and size of MMCs were analyzed by Analysis of Variance (ANOVA) and continued by using Duncan's Multiple Range Test (DMRT) to determine the differences between treatments. The result showed that the concentration of mercury chloride in water affects the metrics profile of spleen MMCs of carp. The number and size of MMCs of carp spleen increased at the concentration of 0.01 mg.l-1 and 0.05 mg.l-1 but decreased at the level of 0.1 mg.l-1 . The results suggest that the profile of MMCs as a non-specific cellular immune response can function as bio-indicators of environmental pollution.